Sediment porewater properties data from Mercer Subglacial Lake - Skidmore, Mark; Dore, John; Tranter, Martyn; Science Team, SALSA; Steigmeyer, August; Michaud, Alexander (IEDA: US Antarctic Program Data Center, 2023)
This dataset contains measurements of sediment porewater properties from cores collected from Mercer Subglacial Lake by the SALSA project. Included are: specific conductance; water stable isotopes (δ2H and δ18O); dissolved gases (methane and its stable isotopes δ13C and δ2H, ethylene, and ethane); and major anions and cations.